Photoinitiators for polymer synthesis : scope, reactivity and efficiency - Fouassier, Jean-Pierre, 1947-; Lalevée, Jacques (Wiley-VCH, 2012)
"Photoinitiating systems for polymerization reactions are largely encountered in a variety of traditional and high-tech sectors, such as radiation curing, (laser) imaging, (micro)electronics, optics, and medicine. This book extensively covers radical and nonradical photoinitiating systems and is divided into four parts: Basic principles in photopolymerization reactions, Radical photoinitiating systems, Nonradical photoinitiating systems, Reactivity of the photoinitiating system."-- Resumé vydavatele
Keywords: polymerizace; fotochemické reakce; polymerization; photochemical reactions; monografie; elektronické knihy; monographs; electronic books